Rapid rural appraisal rational and repertoire - Chambers, Robert (Discussion Paper, 1980)
This paper draws on the papers and discussions of a workshop and of a conference on Rapid Rural Appraisal (RRA). The rationale for RRA is the need in rural development for information that is relevant, timely, accurate and usable. Methods of gathering information are often inefficient, either 'quick-and dirty' as with much rural development tourism, or 'long-and-dirty' as with much conventional social science research. Methods involving trade-offs between relevance, accuracy, and the rigour of greater cost-effectiveness. A repertoire of ten methods illustrates experience and timeliness tend not to be academically respectable, but have ,methods illustrating experience and scope. The key successful RRA is not avoiding superficiality and error, but rather controlling them to achieve cost-effectiveness through optimal ignorance and proportionate accuracy. Time is the most critical factor. Through its sparing demands RRA has potential for releasing time and resources to enable rural appraisers to devote more attention to the rural poor.